Espectroscopia vibracional para avaliação ex vivo da dinâmica das ações induzidas por fungos patogênicos em tecidos biológicos - Morais, Gutierrez Rodrigues de (2016)
In this work the FTIR technique with photoacoustic (FTIR-PAS) detection and the Raman method were used to study the dynamic of the structural changes in lung and liver tissues of Swiss mice submitted to inoculation of the Paracoccidioide brasiliensis fungus (Pb), and in the skin of rats intradermic inoculated by a fraction F1 of Fusarium oxyporyum. Histological evaluation of the samples was performed to validate the results. The experiments were performed ex vivo and as a function of the infection period, evaluating the changes in both optical absorption bands and Raman scattering induced by these pathogens. The study was divided into four parts: 1ª) the Raman spectra of lungs of Swiss mice infected with Pb were correlated with the temporal expression of the gp43 glycoprotein, the apoptosis and the morphological changes. Analyses were performed after 1, 2, 4 and 8 of infection. The bands showed that infection was more intense in the 1st and 4th weeks, and gp43 expression was concomitant with most immunostaining for TUNEL. 2ª) changes in lungs infected with Pb were also evaluated with the FTIR-PAS technique. The results showed that changes in the absorption bands resulted from morphological changes, which were dependent on the infection period. 3ª) FT-Raman technique was used to evaluate the paracoccidioidomycosis in liver of Swiss mice infected with Pb. Changes occurred in the spectral region between 1700-1530 cm-1 and 1370-1290 cm-1, the peaks of phenylalanine and CH2 and CH3 molecules of the collagen. The tissue response resulted in the development of granulomas with yeasts located within macrophages and isolated hepatocytes. 4ª) in this study F1 fraction inoculations were performed in the skin of healthy rats 3, 6, 12 and 24 hours after application of the fraction. The areas of collagens type I and III increased throughout the infection period. There were changes in the areas of the amide I and CH2 and CH3 bands. In conclusion, the present results show that the FTIR, FTIR-PAS and Raman techniques can be combined for evaluation of the dynamics of changes in biological tissues invaded by pathogens, being a promising new way of disease diagnosis.